2004
DOI: 10.1159/000082282
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of the Developing Retina with the Metabotropic Glutamate Agonist APB Induces Long-Term Changes in the Stratification of Retinal Ganglion Cell Dendrites

Abstract: The gradual restriction of initially multistratified retinal ganglion cell (RGC) dendrites into ON and OFF sublaminae of the inner plexiform layer (IPL) can be effectively blocked by treating the developing retina with 2-amino-4-phosphonobutyrate (APB), the metabotropic glutamate agonist, or by light deprivation. Previous studies have focused on the short-term consequences of such manipulations, so the long-term effects of arresting dendritic stratification on the structural development of RGCs are as yet unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…These results provided new insights into the possible synaptic mechanisms with which visual activity regulates the development of RGC dendrites. Fourth, in contrast to assuming that all RGCs with dendrites ramified in both sublaminae a and b of the IPL are regulated by the same mechanism and treated as a single group in our previous study (Tian and Copenhagen, 2003) and several other studies (Bodnarenko and Chalupa, 1993;Bodnarenko et al, 1995;1999;Wang et al, 2001;Deplano et al, 2004;Chalupa and Gü nhan, 2004), we found that the number of RGCs ramified in both sublaminae a and b of the IPL with a single layer of dendritic plexus decreased with age, whereas the number of RGCs ramified in both sublaminae a and b of the IPL with clear bistratified dendritic patterns increased with age. We interpreted these results as indicating that some monostratified ON-OFF RGCs and bistratified RGCs are likely to be in different developmental status and, therefore, ought to be considered separately.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…These results provided new insights into the possible synaptic mechanisms with which visual activity regulates the development of RGC dendrites. Fourth, in contrast to assuming that all RGCs with dendrites ramified in both sublaminae a and b of the IPL are regulated by the same mechanism and treated as a single group in our previous study (Tian and Copenhagen, 2003) and several other studies (Bodnarenko and Chalupa, 1993;Bodnarenko et al, 1995;1999;Wang et al, 2001;Deplano et al, 2004;Chalupa and Gü nhan, 2004), we found that the number of RGCs ramified in both sublaminae a and b of the IPL with a single layer of dendritic plexus decreased with age, whereas the number of RGCs ramified in both sublaminae a and b of the IPL with clear bistratified dendritic patterns increased with age. We interpreted these results as indicating that some monostratified ON-OFF RGCs and bistratified RGCs are likely to be in different developmental status and, therefore, ought to be considered separately.…”
Section: Discussionmentioning
confidence: 74%
“…Several previous studies have investigated the developmental segregation of ON and OFF synaptic pathways in the retina and found that the number of RGCs ramified in both sublaminae a and b of the IPL decreased with age during postnatal development (Bodnarenko and Chalupa, 1993;Bodnarenko et al, 1995Bodnarenko et al, , 1999Wang et al, 2001;Tian and Copenhagen, 2003;Deplano et al, 2004;Chalupa and Gü nhan, 2004). In these studies, all RGCs ramified in both sublaminae a and b of the IPL were considered as a single group regardless of whether their dendrites stratified into a single layer or two layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that visual deprivation might permanently alter retinal circuitry was first suggested by evidence that APB treatment during the first month of postnatal life of the cat induced permanent modifications in RGC function, including an increase in the proportion of RGCs with ON-OFF discharges and loss of surround inhibition (Bisti et al, 1998) and an increase in the percentage of multistratifying RGCs (Deplano et al, 2004). A recent report by Giovanelli et al (2008) showed that in LongEvans rats, early prolonged visual deprivation reduced the spontaneous synaptic activity recorded of RGCs.…”
Section: Long-lasting Effects Of Light Deprivation On Retinal and Othmentioning
confidence: 99%
“…APB has been used in physiological studies to control retinal function and measure its effect using electrophysiological methods such as electroretinography (ERG). In previous studies, APB has been used for both short-term 29 and long-term treatment of the developing retina; the latter involved giving a single dose via intraocular injection daily for 30 days 30 . The same amount of APB (0.092 mg in sterile saline, at a concentration of 50 µM) was used for all injections as suggested in previous work 28,29,31 .…”
Section: Introductionmentioning
confidence: 99%